Effect of laboratory foamer on asphalt foaming characteristics and foamed mixture properties. Issue Volume 18:Issued 4(2017) (3rd April 2017) - Yin, Fan; Arámbula-Mercado, Edith; Newcomb, David
Abstract: In the United States, mechanical foaming is the most popular method for producing warm mix asphalt, which is the latest technology implemented to reduce the production temperature and/or enhance the compactability of asphalt mixtures. Three commonly used commercially available laboratory foamers to produce asphalt foams include the Wirtgen WLB 10S (Wirtgen foamer), the InstroTek Accufoamer (InstroTek foamer) and the Pavement Technology Inc. Foamer (PTI foamer). Though these foamers have been widely used in research studies and construction practice, it is still unknown whether they produce asphalt foams with the same quality and quantity. In this study, asphalt foaming characteristics produced by these three laboratory foamers were measured using a non-contact test set-up consisting of a laser device and a digital camera, and compared in terms of instantaneous volume expansion, foam stability and surface area evolution of foam bubbles. Additionally, the workability, coatability and mechanical performance of foamed mixtures prepared using these same laboratory foamers were compared against the conventional hot mix asphalt (HMA). Test results indicated that foamed asphalts produced by the Wirtgen foamer had the largest volume expansion and greatest foam stability, followed by those produced by the InstroTek foamer and the PTI foamer. The optimum foaming water content ( W opt ) was determined for each laboratory foamer based on the workability and coatability results of the corresponding foamed mixtures. In addition, the performance evaluation of the foamed mixtures produced at W opt values indicated equivalent mixture stiffness but greater moisture susceptibility as compared to the conventional HMA.